Microfluidic Technology for Nucleic Acid Aptamer Evolution and Application. Issue 5 (4th April 2019) - Fraser, Lewis A.; Cheung, Yee‐Wai; Kinghorn, Andrew B.; Guo, Wei; Shiu, Simon Chi‐Chin; Jinata, Chandra; Liu, Mengping; Bhuyan, Soubhagya; Nan, Lang; Shum, Ho Cheung; Tanner, Julian A.
Abstract: The intersection of microfluidics and aptamer technologies holds particular promise for rapid progress in a plethora of applications across biomedical science and other areas. Here, the influence of microfluidics on the field of aptamers, from traditional capillary electrophoresis approaches through innovative modern‐day approaches using micromagnetic beads and emulsion droplets, is reviewed. Miniaturizing aptamer‐based bioassays through microfluidics has the potential to transform diagnostics and embedded biosensing in the coming years. Abstract : This review discusses the advances that microfluidic devices have brought to aptamer research. This includes a discussion of how microfluidics have improved selection strategies and aptamer biosensing technologies.